FRI0236 Ultrasonographic Assessment of Joint Inflammation in Rheumatoid Arthritis: Predictive Value in Response to Tumor Necrosis Factor-α Inhibitor Treatment. (10th June 2014) - Inanc, N.; Ozen, G.; Direskeneli, H.
Abstract : Background: Tumor necrosis factor-α inhibitors (TNFi) are highly effective in patients with RA, while not effective in all, with predictors of response being necessary. Although genetic, inflammatory and serologic biomarkers are under major investigation for this purpose, little is known about the predictive value of ultrasonographic parameters in RA. Objectives: To investigate the ability of ultrasonographic parameters to predict which patients with RA will benefit from the treatment with TNFi in terms of EULAR response. Methods: Biologic-naive RA patients starting treatment with TNFi were examined longitudinally by ultrasonography (US) (Gray-Scale [GS] and Power Doppler [PD]) of 28 joints according to standard scans of EULAR guideline and clinically (Tender/swollen joint count, DAS28, HAQ scores) at baseline and 3rd, 6th and 12th months. US examinations were performed by an experienced sonographer (NI) using MyLab 70 US machine (Esaote, Italy). US synovitis GS and PD signals were semiquantitatively graded from 0 to 3. Total PD and GS synovitis scores of all sites are recorded as sum scores of PD and GS, respectively. The clinical response was evaluated according to the EULAR response criteria at 3rd month. Potential ultrasonographic predictors of response were identified using multivariate binary logistic regression models. Results: The study cohort consisted of 43 RA patients (F/M=34/9, mean disease duration 8.0±6.7 years, mean DAS28 score 5.4±1.1) who were either RF or Anti-CCP positive. Baseline characteristics of TNFi responders (28/43) and non-responders (15/43) are shown in Table 1 . Pain VAS ( P =0.005), sum scores of baseline PD ( P =0.049), GS ( P =0.045) and PD+GS ( P =0.045) differed significantly between responders and non-responders. Baseline PD sum score was the only US parameter in the multivariate analysis predicting which patients achieve good/moderate EULAR response with TNFi at 3rd month (OR=0.9; CI:95% 0.79-0.94, P =0.04). Responders at 3rd month were also more likely to achieve LDA or remission at 1 year ( P =0.019 and P =0.008, respectively). The mean PD and GS sum scores decreased significantly from baseline to 3rd month ( P <0.001 for both) whereas decrease between 3rd and 6th months was nonsignificant ( P =0.68 and P =0.77, respectively). Conclusions: Our data underline that baseline PD scores, despite similar clinical features, can predict which patients will respond to TNFi therapy. Responders at 3rd month mostly preserve initial response and more likely to achieve LDA at 1 year. Ultrasonographic response to TNFi treatment can be achieved substantially in the first 3 months. Beyond 3rd month changes in US scores are mostly nonsignificant. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1918